2001
DOI: 10.1073/pnas.231496298
|View full text |Cite
|
Sign up to set email alerts
|

Suppressed kindling epileptogenesis in mice with ectopic overexpression of galanin

Abstract: The neuropeptide galanin has been shown to suppress epileptic seizures. In cortical and hippocampal areas, galanin is normally mainly expressed in noradrenergic afferents. We have generated a mouse overexpressing galanin in neurons under the plateletderived growth factor B promoter. RIA and HPLC analysis revealed up to 8-fold higher levels of galanin in transgenic as compared with wild-type mice. Ectopic galanin overexpression was detected especially in dentate granule cells and hippocampal and cortical pyrami… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
94
0

Year Published

2004
2004
2012
2012

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 103 publications
(105 citation statements)
references
References 56 publications
11
94
0
Order By: Relevance
“…Further incubation with Streptavidine-HRP, biotinyl tyramide reagent and Alexa-488 fluorophore finalized the reaction. The specificity of antibody binding was confirmed by omission 11 of the primary antibody on a subset of sections (Kokaia, M., Holmberg, K., et al 2001;Kuteeva, E., Calza, L., et al 2004).…”
Section: Immunohistochemistrymentioning
confidence: 91%
See 4 more Smart Citations
“…Further incubation with Streptavidine-HRP, biotinyl tyramide reagent and Alexa-488 fluorophore finalized the reaction. The specificity of antibody binding was confirmed by omission 11 of the primary antibody on a subset of sections (Kokaia, M., Holmberg, K., et al 2001;Kuteeva, E., Calza, L., et al 2004).…”
Section: Immunohistochemistrymentioning
confidence: 91%
“…GalOE mice were generated as described earlier (Kokaia, M., Holmberg, K., et al 2001), and the transgenic status of animals was confirmed by PCR (Kokaia, M., Holmberg, K., et al 2001). All experiments were performed according to National Institutes of Health guidelines and approved by the local Ethical Committee.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations